From cannibalism to empowerment: An analects-inspired attempt to balance community and liberty - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2004)
The Confucian tradition has often been credited with a strong allegiance to the value of community. It recognizes that certain goods might be attained through special forms of human association, but not by any solitary individual. Are such community goods attained at the expense of the liberty of individual members? Philosophers have struggled with the tension between liberty and community since the dawn of Western philosophy. Aristotle complained about the false idea of liberty as "doing what one likes," which is contradictory to the true interests of the polis.2 Such lib- erty, or rather license, is undoubtedly detrimental to any peaceful coexistence, not to say the harmonious and mutually beneficial association of community. Without regulation, such license would, according to Thomas Hobbes, result in a "war of all against all," making life "solitary, poor, nasty, brutish and sho